Penguatan Akhlak dan Etika Digital Pelajar Melalui Seminar Pendidikan Berbasis Partisipatif di Ma Nurul Jadid Bungbaruh Kadur Pamekasan - Mohammad Zakki; Badrut Tamam (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2026)
The rapid development of digital technology has significantly influenced students’ behavior and patterns of social interaction, particularly in the use of social media and everyday communication ethics. This condition presents a challenge for educational institutions in strengthening students’ moral values and character formation in the digital era. This community engagement program aimed to enhance students’ moral awareness through a participatory moral education seminar conducted at MA Nurul Jadid Bungbaruh Kadur, Pamekasan. The program was implemented through lectures, interactive discussions, and reflective learning activities involving 52 senior high school students (MA level). The evaluation employed observation, questionnaires, and pre-test and post-test assessments to measure changes in participants’ understanding. The findings indicate an improvement in students’ comprehension across several key indicators, particularly regarding social media ethics, learning motivation, and awareness of the importance of moral conduct in daily life. Furthermore, most participants responded positively to the seminar, considering the materials relevant to their experiences as adolescents. The participatory approach also contributed to creating a more communicative and reflective learning environment. Therefore, participatory moral education seminars demonstrate considerable potential as an effective medium for strengthening students’ character development and promoting ethical digital behavior in both school and madrasah settings.